A highly efficient metal-free hydrocarbonylation of alkynes with propargylamines and water. Issue 5 (16th February 2022) - Xie, Yujuan; Huang, Liliang; Qi, Yayu; Hu, Junduo; Song, Liangliang; Feng, Huangdi
Abstract : A catalyst- and solvent-free, highly efficient, atom-economical synthesis strategy has been developed for the construction of 1, 4-dicarbonyl motifs via hydrocarbonylation of alkynes with propargylamines and water. Abstract : Metal-catalyzed hydrocarbofunctionalizations of alkynes or alkenes are well established. In contrast, metal-free strategies have few precedents. We report herein a multicomponent reaction that generates functionalized 1, 4-dicarbonyl motifs via formal hydrocarbonylation of activated alkynes with propargylamines and water under metal-free conditions. This novel synthesis method utilizes propargylamines and water as carbonyl and proton precursors in which propargylamines are activated in situ by alkynes for α-C(sp 3 )–H activation and C–N bond cleavage. This method exhibits simple and mild conditions, high efficiency, and good functional group tolerance. Meanwhile, it represents a general strategy for the merger of C–N bond activation with hydrocarbonylation of unsaturated hydrocarbons.